CARLOS SENA: A TRAJETÓRIA DE UM ARTISTA NA ARTE GOIANA (1980-1989) - COELHO, Armando de Aguiar Guedes (2009)
This research CARLOS SENA: THE ARTIST STEPS INTO THE GOIÂNIA ART SCENE (1980-1989) focuses on Carlos Sena s professional status and productions of plastic arts in the goianiense visual arts community from the 80s. He is known for his many group expositions and private art shows, festival awards, and being an active member of the art jury at festivals. He is also well known for his intense production in painting, which was divided into two phases. The first phase being the first half of the 80s and the second being the other half of the decade. This period revealed an artist who dedicated the same posture to technician in drawing and painting as in experimental arts. During this time, it is possible to observe into the Carlos Sena´s iconography, several symbolisms which dialogue with several discussions from the period, as sexuality, mass media, and symbolic power. The analysis of Sena´s paintings of this time follows the analysis system adopted from the authors Ferreira Gullar e Gaston Bachelard. It happened to be during his painting production in the 80s, that arts career became a professional job in Goiânia, conducting the research to verify the connection between the art work and market structure. This research presents the Goiânia artistic scenario from the 80s that focuses on Carlos Sena´s presence and artist market from the period.